2009
DOI: 10.1590/s1676-06032009000100010
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura populacional de Macrobrachium potiuna (Crustacea, Palaemonidae) no Rio do Moinho, Mangaratiba, Rio de Janeiro, Brasil

Abstract: Population structure of Macrobrachium potiuna (Crustacea, Palaemonidae) in the Moinho's River, Mangaratiba, Rio de Janeiro, Brazil. Biota Neotrop. 9(1): http://www. biotaneotropica.org.br/v9n1/en/abstract?article+bn01309012009. (Müller, 1880) were collected in the Moinhos' River from July 2001 to June 2002. The aim of this study was providing some information about the population structure of this species. In the laboratory, the shrimps were sexed, measured and classified according to developmental stages: ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 17 publications
4
23
0
10
Order By: Relevance
“…By ruling out hermaphroditism, variations in the sex ratio of populations of Macrobrachium spp. might be explained by other factors, for instance: differences in migration rates, mortality, longevity and growth between the sexes (Wenner, 1972;Souza and Fontoura, 1996;Mantel and Dudgeon, 2005;Mattos and Oshiro, 2009), and different reproductive strategies (Mossolin and Bueno, 2002;Hayd and Anger, 2013;Rocha et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…By ruling out hermaphroditism, variations in the sex ratio of populations of Macrobrachium spp. might be explained by other factors, for instance: differences in migration rates, mortality, longevity and growth between the sexes (Wenner, 1972;Souza and Fontoura, 1996;Mantel and Dudgeon, 2005;Mattos and Oshiro, 2009), and different reproductive strategies (Mossolin and Bueno, 2002;Hayd and Anger, 2013;Rocha et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Decapods, and especially shrimps look to be scarce and present a restricted distribution in Guapiacú river catchment when compared with other coastal catchments (Ammar et al, 2001;Mattos and Oshiro, 2009;Silveira, 1997), but this is difficult to confirm due to differences in sampling techniques. We found species that have different reproductive strategies: Trichodactylidae crabs and M. potiuna shrimp are freshwater specialized species that have the entire life cycle in freshwater, while M. olfersii and M. carcinus are amphidromous (Silveira, 1997) and depend on estuarine brackish water for the development of the first stages of larval growth.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, stream size variation is a key factor influencing community structure of invertebrates (Cargnin-Ferreira and Forsberg, 2000), and fishes (Magalhães et al, 2002). Although the RCC does not make specific predictions regarding crustacean fauna, it may also be strongly influenced by these variations along the river course, but its relation is poorly studied, especially with respect to species inhabiting Atlantic forest streams (Mattos and Oshiro, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence and abundance of various species of decapod crustaceans are limited by environmental factors such as temperature and salinity, as in the case of M. potiuna (Müller, 1880), which was studied by Mattos and Oshiro (2009). These authors concluded that the predominance of immature shrimps during the months in which the water temperature did not exceed 21 °C indicated the close relationship between this abiotic factor and growth of individuals.…”
Section: Discussionmentioning
confidence: 99%